Navigating Knowledge: a user study to support the creation of a community library in Vila do Coqueiro, a traditional fishing community in Luís Correia, Brazil. (Cadernos de Sociomuseologia, 2026)
Coqueiro, a traditional fishing community in Luís Correia, Brazil. This article presents the findings of a user study conducted in the traditional community of Vila do Coqueiro (Piauí, Brazil), aimed at supporting the creation of a community library linked to the Museu da Vila—an extension of the Ecomuseum of the Parnaíba Delta and headquarters of the Graduate Program in Arts, Heritage, and Museology (PPGAPM/UFDPar). The research is grounded in the theoretical frameworks of critical librarianship, Southern epistemologies, and social museology, seeking to understand the community's informational needs, sociocultural profiles, and expectations regarding access to information and culture. The methodology included direct territorial observation, informal conversations, and the application of a semi-structured questionnaire composed of open- and closed-ended questions, answered by 28 participants. The data revealed a high level of community receptiveness to the proposal. The unanimous positive assessment regarding the library’s potential educational and cultural impact underscores both its social legitimacy and its transformative potential. Participants expressed a strong willingness to engage in the development and use of the space, reinforcing the feasibility of a collaborative management model. The responses indicated a collective aspiration for a hybrid, multimodal library that integrates books, digital resources, workshops, and spaces for community interaction—thus positioning the library as a site of belonging, care, and emancipation. It is concluded that the proposed community library, emerging from the voices and needs of the territory, constitutes a replicable social technology capable of articulating information, memory, and cognitive justice. The methodological experience becomes, therefore, a reference for the development of sustainable cultural policies in traditional communities.Keywords: community library; user study; critical librarianship; social museology; cognitive justice.